2019
DOI: 10.1051/0004-6361/201936253
|View full text |Cite
|
Sign up to set email alerts
|

Formation of coronal rain triggered by impulsive heating associated with magnetic reconnection

Abstract: Context. Coronal rain consists of cool plasma condensations formed in coronal loops as a result of thermal instability. The standard models of coronal rain formation assume that the heating is quasi-steady and localised at the coronal loop footpoints. Aims. We present an observation of magnetic reconnection in the corona and the associated impulsive heating triggering formation of coronal rain condensations. Methods. We analyse combined SDO/AIA and IRIS observations of a coronal rain event following a reconnec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…In this scenario, interchange reconnection between open and closed loops is invoked to explain the presence of coronal rain within the closed loops, although it is yet unclear if reconnection itself plays a direct role in the generation of coronal rain. This seems indeed possible, as suggested by IRIS observations from Kohutova, Verwichte, and Froment (2019).…”
Section: Coronal Rainmentioning
confidence: 61%
“…In this scenario, interchange reconnection between open and closed loops is invoked to explain the presence of coronal rain within the closed loops, although it is yet unclear if reconnection itself plays a direct role in the generation of coronal rain. This seems indeed possible, as suggested by IRIS observations from Kohutova, Verwichte, and Froment (2019).…”
Section: Coronal Rainmentioning
confidence: 61%
“…This IRIS dataset has been previously analysed by Kohutova et al (2019) and Schad (2018) with a focus on coronal rain. In particular, Kohutova et al (2019) performed a detailed analysis of the reconnection event, the onset of thermal instability and associated coronal rain formation in one of the coronal loops. The analysis therein however excluded the upward-moving surge material and the associated downflows.…”
Section: Observationmentioning
confidence: 99%
“…Its quantitative role in the mass cycle and heating of the solar atmosphere has yet to be determined. Recent works have shown that apart from stratified heating in the atmosphere leading to TNE and, thus, evaporation-condensation cycles, other ways may exist to reach this rain-triggering thermal instability: magnetic reconnection between open-structure and low-lying closed loops (Liu et al 2016;Li et al 2018), interchange reconnection in null-point topologies (Mason et al 2019), and reconnection-induced localised heating (Kohutova et al 2019). Due to their recent discovery, the details of the mechanisms that take place in such configurations are currently unclear.…”
Section: Contextmentioning
confidence: 99%